When Ballistics meet Anthropology: A case study from the Medieval archaeological site Our Lady of Mountain church in Lobor (Croatia) - Hincak, Zdravka; Filipec, Krešimir; Špoljarić, Igor; Gršković, Branka; Mršić, Gordan; Popović, Maja; Mikulka, Ana (2014)
During the summer archaeological excavation in 2012, on the site Our Lady of the Mountain church in Lobor, the grave number 888 was revealed, with skeletal remains of a young male person. The very position of the grave in a gothic church, along the apsidal area, accentuate the status of this person in the society. The apse as a remain of the gothic church elements is part of multi-stratified layers, maybe of a vertical complex where it is possible to separate structures from the 3rd to the 17th century, with the church Our Lady of the Mountain in Lobor as the last layer. It was a primary burial, with a position of the grave following the church’s orientation East-West. The anthropological analysis was performed: determination of sex and age at death, body height, description of pathological conditions and eventual musculo-skeletal stress markers. On the skeletal remains circular defects were detected, in forms of a penetrating trauma due to a spherical or spheroid body or object activity. These fragments of uneven dimensions were embedded in the bones: right tibial bone, left and right femoral bone. With application of a scanning electron microscopy (Scanning Electron Microscopy / Energy Dispersive Spectroscopy method, SEM/EDX) and X-ray fluorescence spectroscopy (Micro X-ray fluorescence method, µXRF) a chemical analysis of the elements, together with morphological 2D and 3D characterization of samples were obtained.